Comparison of the effects of progressive supervised and home program exercise therapy in mild-moderate hallux valgus - Merve Betul Oztarsu; Sevim Oksuz (Becaris Publishing Limited, 2023)
Aim: To compare the effects of progressive exercise therapy, performed under the supervision of a physiotherapist and given as a home program in individuals with hallux valgus. Methods: Participants were randomly divided into two groups. While one group performed the exercises under the supervision of a physiotherapist, the other group did the same program at home. Results: The amount of decrease in foot adduction angle, pain level while walking, and right foot navicular height of individuals receiving treatment under the supervision of a physiotherapist were significantly higher. Conclusion: The exercise program applied under the supervision of a physiotherapist was more effective in reducing the first toe adduction angle, medial longitudinal arc height, and pain, improving dynamic balance and functional capacity.